Electronic delivery of the locality-based solutions - Fabian, Peter (Univerzita Pardubice, 2001)
An incrementally implemented, multi-layred architecture, which embraces existing and new systems, offers large potential. A well-designed platform encompassing databases of common geographically related features and assets would enable organizations to be more efficient, flexible and consistent. They would be better equipped to respond both to citizens and to future government requirements.
Keywords: Informační technologie; elektronické dokumenty; místní správa; veřejná informatika; administrativa; Databáze